2003
DOI: 10.1111/j.1442-1984.2003.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of population spatial structure on the quantity and quality of seeds set byPrimula sieboldii(Primulaceae)

Abstract: Effects of spatial population structure on the reproductive success of Primula sieboldii E. Morren, an endangered heterostylous perennial, were studied through the analysis of quantity and quality of seeds in a natural habitat in central Japan. Seed set of individual flowering ramets varied significantly depending on the degrees of isolation from their potential mates. The flowering ramets, which have the opposite-morph ramets within 5 m, set significantly higher mean seeds per flower (approx. 15) than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 72 publications
(100 reference statements)
2
18
0
Order By: Relevance
“…The seed production patterns in the present study agree with the results of several previous studies (Nishihiro et al 2000;Ishihama et al 2003;Watanabe et al 2003) For example. Watanabe et al (2003) reported that the number of the opposite morph genets within a patch had a significant effect on the seed set of P. sieboldii for 2 years regardless of morph.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The seed production patterns in the present study agree with the results of several previous studies (Nishihiro et al 2000;Ishihama et al 2003;Watanabe et al 2003) For example. Watanabe et al (2003) reported that the number of the opposite morph genets within a patch had a significant effect on the seed set of P. sieboldii for 2 years regardless of morph.…”
Section: Discussionsupporting
confidence: 95%
“…However, hand pollination experiments found that some plants have partial self-compatibility although the number of seeds set by self-fertilization is much lower than that by pollen from the different morph (Matsumura and Washitani 2000). In natural populations of P. sieboldii, the amount of pollen on the stigma, the seed set, and the survival rate of seedlings are low in mother plants when there are low population densities of neighbouring opposite-morph plants (Nishihiro et al 2000;Watanabe et al 2003). Although these results strongly suggest the existence of pollen limitation and inbreeding depression caused by selfing, knowledge of the effect of spatial structure was incomplete because the actual mating pattern was unknown.…”
Section: Introductionmentioning
confidence: 97%
“…However, in small and isolated populations biased morph ratios may be generated stochastically resulting in the deficiency of compatible mates or pollen. This can significantly reduce reproductive success (Fischer et al 2003, Kéry et al 2003, Matsumura and Washitani 2000 and increase genetic drift and inbreeding, leading to genetic erosion and/or inbreeding depression (Van Rossum and Triest 2006a, Watanabe et al 2003). Pollination failure may lead to breakdown of the self-incompatibility system, giving mating advantage for the most self-fertile morph, but at the same time increasing the risk of inbreeding depression (Glémin et al 2001, Mateu-Andrés and Segarra-Moragues 2004, Porcher and Lande 2005.…”
Section: Regional Scale Population Structurementioning
confidence: 96%
“…In some natural populations of P. sieboldii, a strong effect of opposite-morph density within a 5 m radius on the seed set was found (Nishihiro et al 2000;Watanabe et al 2003), implicating relatively short pollen-dispersal distance and the possible importance of the local arrangement of genetically compatible mates for successful seed reproduction.…”
Section: Pollen Flow Measurements In Experimental Populations With DImentioning
confidence: 99%
“…Most remaining populations of the species are more or less isolated due to habitat fragmentation (Environment Agency of Japan 2000), but variously sized populations differing greatly with regarding to extinction probability and genetic diversity still remain. A relatively sufficient amount of data on the demographic, eco-physiological, and genetic traits of the species is available, most of which has been obtained from wild populations in Southern Hokkaido or central Honshu (Washitani et al 1991(Washitani et al , 1994a(Washitani et al , 1994bKakishima et al 1995;Washitani 1996;Nishihiro et al 2000;Washitani 2000, 2002;Okayama et al 2003;Ishihama et al 2003Ishihama et al , 2005Watanabe et al 2003;Noda et al 2004;Honjo et al 2004;Kitamoto et al 2005).…”
Section: Primula Sieboldii and Primula Modesta As Modelsmentioning
confidence: 99%